The model of mobile payment system acceptance on social networks in Thailand: A conceptual framework - Chaveesuk, Singha; Wutthirong, Phayat; Chaiyasoonthorn, Wornchanok (My University, 2018)
Mobile technologies and social media are rapidly increasing and initiating to provide interesting and beneficial new products or services. This technology has led to a significant revolution in modern trading systems towards more successful commercial formats. With these innovative technologies, mobile commerce or social commerce is used as successfully commercial formats to achieve their sales and profits. To gain attention in global, mobile payment (m-payment) has changed to become a key activity for digital economy. The m-payment system enables users to pay for goods or services. The Thai government policy promotes the use of mobile payment services. However, these m-payment services are now undergoing the adoption process. More and more consumers use their mobile applications however the new method of financial payment has had limited consumer interest. Adopting m-payment is relatively low compared to the adoption of recent forms of payments. Limited research has been undertaken to identify the factors affecting the use of the mobile payment in the new electronic environment. Drawing on the technology acceptance model, IS success model, and trust, this research is to develop a conceptual framework to analyze users’ acceptance of m-payment systems on social networks for identifying and explaining potential factors affecting intention to use and user satisfaction of m-payment, together with the mediating effect of usability towards the actual use of mobile payment on social networks.
Keywords: IS success model; Mobile payment acceptance model; Social networks; TAM; Trust